Identifying Key Determinants of Entrepreneurial Intention: Integrating TPB and Religiosity Among Islamic University Students in Yogyakarta - Haidar Daffa; Rheyza Virgiawan; Rosyad Denhas Mohamad (Al-Tijary, 2025)
This study aims to examine the influence of religiosity and the Theory of Planned Behavior (TPB) model on entrepreneurial intention among students at Islamic universities in Yogyakarta. The data collection was conducted from January to March 2024 using a purposive sampling method, resulting in 252 respondents. A quantitative research design was employed, with data gathered through an online questionnaire distributed via Google Forms. The data were analyzed using SmartPLS version 4.1.0.1. The study found that independent attitude (X1) and religiosity (X4) did not have a significant influence on students' entrepreneurial intention. In contrast, entrepreneurial knowledge (X2) and motivation (X3) were found to significantly influence students’ intention to engage in entrepreneurship. These results suggest that, compared to independent attitude and religiosity, entrepreneurial knowledge and motivation play a more substantial role in shaping entrepreneurial intention among students at Islamic universities in Yogyakarta.